Beliefs of Israeli Family Caregivers of People with Dementia toward Advance Care Planning. Issue 3 (2nd July 2020) - Kermel-Schiffman, Ile; Werner, Perla
Abstract: Family caregivers of people with dementia often must make crucial medical decisions for them that may increase the burden of care experienced. Although undertaking Advance Care Planning (ACP) might reduce their decision-making burden, completion rates remain very low. The present study aimed to explore the common beliefs of family caregivers of people with dementia about undertaking ACP for themselves. A qualitative study was conducted, using a semi-structured questionnaire based on the Theory of Planned Behavior. Face-to-face interviews were conducted with a convenience sample of 20 family caregivers of people with dementia in Israel. The behavioral beliefs expressed by the participants referred to the dual benefits of ACP, for the person who will not be able to make medical decisions at the end of life and for themselves. Participants mentioned that family members and friends were the main persons with whom they would consult in making decisions regarding ACP. Personal characteristics and instrumental factors were mentioned as enablers and barriers to undertaking ACP. Findings from the study provide an important basis for expanding research and for developing interventions that can encourage undertaking ACP.